Art after Instagram : art spaces, audiences, aesthetics - MacDowall, Lachlan, 1974-; Budge, Kylie (Routledge advances in art and visual studies., 2022)
"This book explores the effects of the Instagram platform on the making and viewing of art. Authors Lachlan MacDowall and Kylie Budge critically analyse the ways Instagram has influenced artists, art spaces, art institutions, and art audiences, and ultimately contemporary aesthetic experience. The book argues that more than simply being a container for digital photography, the architecture of Instagram represents a new relationship to the image and to visual experience, a way of shaping ocular habits and social relations. Following a detailed analysis of the structure of Instagram - the tactile world of affiliation ('follows'), aesthetics ('likes') and attention ('comments') - the book examines how art spaces, audiences and aesthetics are key to understanding its rise. The book will be of interest to scholars working in art history, design, digital culture, cultural studies, sociology, education, business, media and communication studies"- Resumé vydavatel